Optics-Integrated Microfluidic Platforms for Biomolecular Analyses - Bates, Kathleen E. (Biophys J, 2016)
Compared with conventional optical methods, optics implemented on microfluidic chips provide small, and often much cheaper ways to interrogate biological systems from the level of single molecules up to small model organisms. The optical probing of single molecules has been used to investigate the mechanical properties of individual biological molecules; however, multiplexing of these measurements through microfluidics and nanofluidics confers many analytical advantages. Optics-integrated microfluidic systems can significantly simplify sample processing and allow a more user-friendly experience; alignments of on-chip optical components are predetermined during fabrication and many purely optical techniques are passively controlled. Furthermore, sample loss from complicated preparation and fluid transfer steps can be virtually eliminated, a particularly important attribute for biological molecules at very low concentrations. Excellent fluid handling and high surface area/volume ratios also contribute to faster detection times for low abundance molecules in small sample volumes. Although integration of optical systems with classical microfluidic analysis techniques has been limited, microfluidics offers a ready platform for interrogation of biophysical properties. By exploiting the ease with which fluids and particles can be precisely and dynamically controlled in microfluidic devices, optical sensors capable of unique imaging modes, single molecule manipulation, and detection of minute changes in concentration of an analyte are possible.